Interfacial reaction between SAC305 lead–free solders and ENImAg surface finish and bare copper - M.A., Rabiatul Adawiyah; O., Saliza Azlina (Wiley, 2017)
Different surface finishes on printed circuit board strongly influence the formation of intermetallic compounds (IMCs), and solder joint reliability. In this paper the effect of two different substrates namely electroless nickel/immersion silver (ENImAg) and bare copper on interfacial reaction when exposed to a reflow soldering process are presented. The result revealed that the black line nickel disappeared on the electroless nickel/immersion silver surface finish after the plating process. Subsequently, the intermetallic compound formed on electroless nickel/immersion silver surface finish are (Cu,Ni)6Sn5, and (Ni,Cu)3Sn4 with a chuck-shape, rode-type, and needle-shape after reflow soldering. Meanwhile, only Cu6Sn5 layer is found on bare copper with a spherical-shape. The results also indicated that different surface finishes are affected by the growth of intermetallic formation and shear strength, where tin-3.0silver-copper0.5/copper (SAC305/Cu) produced a thicker intermetallic layer, larger grain size, and less shear strength compared with tin-3.0silver-copper0.5/electroless nickel immersion silver (SAC305/ENImAg) surface finish.